Perancangan dan Simulasi Smart Greenhouse Mini Menggunakan Arduino Uno untuk Pengendalian Suhu, Intensitas Cahaya, dan Kelembapan Tanah - Ungkap Hutasoit; Windi Andriani; Benjamin Silalahi; Jastin Pangaribuan; Eka Dodi Suryanto; Dian Putra Saragi (Kampus Akademik Publiser, 2026)
This study designs a Smart Greenhouse Mini based on Arduino Uno to automatically monitor and control temperature, soil moisture, light intensity, and rain conditions. The system uses several sensors integrated with actuators such as a fan, water pump, LED light, and stepper motor. The results show that the system can automatically maintain optimal greenhouse conditions and improve plant management efficiency.